UJI DAYA KECAMBAH PADA BENIH PADI (Oryza sativa L.) Di BADAN STANDARISASI INSTURMRN PERTANIAN (BSIP) NAIBONAT NUSA TENGGARA TIMUR - Duanita Stefania Dengga; Nur Aini Bunyani; Abdonia W. Finmeta; Nardi M. Leo; Eka Citra Gayatri Kerihi (Adisam Publisher, 2025)
This research was conducted at the Agricultural Instrument Standardization Agency (BSIP) in East Nusa Tenggara from March 5 to May 5, 2024. The objective was to determine the effect of germination on rice seeds using naturals stimulants such as water, coconut water, and aloe vera gel The method used was a germination test on moist tissue media in a closed container, with daily application of treatments for seven days. Three types of natural stimulants were used in the study: water, aloe vera gel, and coconut water, applied to two rice varieties, Inpari 48 Blass and IP 6 Jete. Observed parameters included germination rate, uniformity of growth, primary root length, and secondary root development. The results showed that water yielded the highest germination rate, followed by aloe vera gel, while coconut water produced the lowest results. Aloe vera gel was also more effective in stimulating root growth compared to coconut water. This is presumably due to the decline of active compounds in coconut water as a result of storage. Therefore, aloe vera gel and coconut water can be used as alternative natural stimulants to improve seed quality, with aloe vera gel showing superior results.